2011
DOI: 10.3390/md9101731
|View full text |Cite
|
Sign up to set email alerts
|

Therapies from Fucoidan; Multifunctional Marine Polymers

Abstract: Published research on fucoidans increased three fold between 2000 and 2010. These algal derived marine carbohydrate polymers present numerous valuable bioactivities. This review discusses the role for fucoidan in the control of acute and chronic inflammation via selectin blockade, enzyme inhibition and inhibiting the complement cascade. The recent data on toxicology and uptake of fucoidan is detailed together with a discussion on the comparative activities of fractions of fucoidan from different sources. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
225
0
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(246 citation statements)
references
References 118 publications
3
225
0
15
Order By: Relevance
“…Natural fucoidan has been reported to inhibit coated viruses such as HSV by blocking receptor-mediated entry and interfering with replication. 48 To determine whether these antiviral activities are retained in our synthetic glycopolymers, we tested the drug effect of glycopolymers in HSV-1-infected HCECs.…”
Section: Resultsmentioning
confidence: 99%
“…Natural fucoidan has been reported to inhibit coated viruses such as HSV by blocking receptor-mediated entry and interfering with replication. 48 To determine whether these antiviral activities are retained in our synthetic glycopolymers, we tested the drug effect of glycopolymers in HSV-1-infected HCECs.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of biological activities of fucoidan varies with species, molecular weight, composition, structure and the route of extraction (Fitton 2011), and its non-animal origin brings particular pharmacological activities (Senni et al 2006). Fucoidan has been well studied for its antitumor (Hsu et al 2013), antiviral (Tengdelius et al 2014), anti-inflammatory (Hwang et al 2011), and anticoagulant (Irhimeh et al 2009) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan, a class of fucose-enriched sulfated polysaccharides, is a naturally occurring polysaccharide compound in brown alga, such as Fucus vesiculosus, Cladosiphon okamuranus and Laminaria saccharina [1,2] . It has recently been reported that fucoidan possesses a wide variety of biological activities, including anticoagulant, antiviral, antiangiogenic, anticancer and immune-modulatory activities [3] .…”
Section: Introductionmentioning
confidence: 99%